The Association between Hypothyroidism and Mental Health: A Literature Review - Dubniewicz, Ewa; Majewska, Paula; Staszek, Alicja; Łoskot, Wiktoria; Szwech, Jan; Matczak, Mateusz; Jasiński, Karol; Broda, Aleksandra; Hoksa, Kacper; Jodłowski, Krzysztof (Journal of Education, Health and Sport, 2025)
Introduction and purpose: Hypothyroidism, characterized by reduced thyroid hormone production, is a common condition in patients. It can impact various bodily functions and beyond physical symptoms, significantly impacts mental health, contributing to conditions such as depression, anxiety, and cognitive impairment. This article explores the relationship between hypothyroidism and mental disorders, examining underlying mechanisms, clinical correlations, and management strategies to improve outcomes for affected individuals. State of knowledge: It is well-established in scientific literature that hypothyroidism is strongly linked to mental health issues. Thyroid hormones play a key role in brain function, and their deficiency can disrupt mood regulation and cognitive process. Autoimmune thyroiditis, such as Hashimoto’s disease, further links hypothyroidism to mood disorders due to chronic inflammation and autoimmunity. Treatment with levothyroxine often improves symptoms, highlighting the thyroid’s critical role in mental health. However, the mechanisms remain under active investigation, with ongoing research into thyroid-brain interactions. Conclusion: The correlation between hypothyroidism and mental disorders underscores the importance of recognizing thyroid dysfunction in psychiatric assessments. Early diagnosis and appropriate management of hypothyroidism can significantly improve mental health outcomes, emphasizing the critical interplay between endocrine and psychiatric health.